2022
DOI: 10.1080/13603116.2022.2119290
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated instruction: ‘to be, or not to be, that is the question’

Abstract: Education systems around the world, faces the major challenge of including all children in schools. Differentiated instruction (DI) is proposed as a pedagogical approach that support social, emotional and academic success for all students in the context of heterogeneous classrooms. Although, recent research draws the attention to the inconsistent definitions and practices of DI. In this context, this qualitative study aimed at exploring the Portuguese teachers self-reported typical DI practices in mixedability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Since various data collection tools are used in the studies, data analysis methods also vary. a4,a5,a6,a8,a11,a12,a14,a19,a20,a25,a28,a35,a36,a37 Children and teacher 13 31.7 a2,a9,a16,a17,a21,a23,a24,a26,a27,a30,a31,a34 Table 8, it is found that the most studied groups were "teachers" (36.6%), followed by "children and teachers" (31.7%). These sample groups were followed by "children" (14.6%) and "prospective teachers" (4.9%), and the least studied groups were "teachers and school administrators" (2.4%) and "children, teachers and school administrators" (2.4%).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Since various data collection tools are used in the studies, data analysis methods also vary. a4,a5,a6,a8,a11,a12,a14,a19,a20,a25,a28,a35,a36,a37 Children and teacher 13 31.7 a2,a9,a16,a17,a21,a23,a24,a26,a27,a30,a31,a34 Table 8, it is found that the most studied groups were "teachers" (36.6%), followed by "children and teachers" (31.7%). These sample groups were followed by "children" (14.6%) and "prospective teachers" (4.9%), and the least studied groups were "teachers and school administrators" (2.4%) and "children, teachers and school administrators" (2.4%).…”
Section: Resultsmentioning
confidence: 93%
“…It is seen that differentiated instructional approach studies in preschool education are mostly published in SCI/SSCI index journals. a7,a12,a14,a15,a19,a20,a23,a28,a29,a32,a33,a34,a37,a38,a39,a40,a41,Quantitative 13 31.7 a4,a5,a6,a8,a9,a13,a16,a18,a21,a22,a25,a26 Table 3, it is seen that qualitative designs (43.9%) were used the most in the studies, followed by quantitative (31.7%) and mixed (24.4%) designs, respectively. Table 4, it is seen that there are five full experimental studies, four quasi-experimental studies, three survey studies and two studies using correlation method among the studies conducted in the experimental method using quantitative design.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is seen that differentiated instructional approach studies in preschool education are mostly published in SCI/SSCI index journals. a7,a12,a14,a15,a19,a20,a23,a28,a29,a32,a33,a34,a37,a38,a39,a40,a41,Quantitative 13 31.7 a4,a5,a6,a8,a9,a13,a16,a18,a21,a22,a25,a26, a36 Mixed 10 24.4 a1, a2,…”
Section: Resultsmentioning
confidence: 99%
“…This transformation demands that educators employ multifaceted instructional approaches to cater to the variegated needs of their classrooms (Hoover and DeBettencourt, 2018). Besides, the use of differentiated education, namely using tiered instructions, has been a well-established pedagogical approach utilized to address the varying requirements of students (Gaitas et al, 2022). Tiered instructions have risen to the challenge, presenting a pedagogically sound methodology that considers students' varying abilities and readiness levels.…”
Section: Introductionmentioning
confidence: 99%